Training legal translators and interpreters: Creation and reception of didactic materials and resources to train non-professional translators and interpreters in languages of lesser diffusion - Bayón Cenitagoya, Candelas; Sanz de la Rosa, Andrea (Estudios de Traducción, 2026)
Amidst the shift in migratory paradigms, the Erasmus+ project Dialogos aims to offer a solution to linguistic barriers faced by migrant population when it comes to accessing Public Services. Said barriers are even more significant in the case of Languages of Lesser Diffusion (LLD) speakers, for which there is a lack of qualified linguistic professionals and, thus, ad hoc interpreters with no formal training are drawn on. This results in inequalities in accessing services like healthcare or legal assistance. In this context, Dialogos suggests the creation of a training course in Public Service Interpreting and Translation (PSIT) addressed to LLD speakers, to enable them to provide quality linguistic assistance. This paper focuses on analysing the materials designed as part of the legal-administrative module of the course, as well as the didactic methodologies adopted. We will also consider the feedback received from the attendants of the pilot course, which took place on March 2024 in Madrid. Our main objective is to present the methodology for materials creation and PSIT training, with special emphasis on the legal field and its peculiarities. Additionally, in line with the project’s general objectives, we aim at contributing to the inclusion of migrant population in the host society and the professionalisation of PSIT.